Manfaat “Rekam Medis Elektronik” Ditinjau dari Manfaat Ekonomi, Klinis, dan Informasi Klinis di Rumah Sakit - Novita Ariyanti; Farid Agushybana; Aris Puji Widodo (Jurnal Kesehatan Komunitas, 2023)
The development and progress of information technology are advancing very rapidly, electronic medical records are one form of these developments and advances in the health sector. A hospital is a place of service in the health sector that performs services related to medical records. Medical records can be made in full and clearly in electronic (digital) form. The implementation of medical record technology can solve many problems in the economic field, clinical, and information of clinical in the hospital system. The high cost of operational and complicated procedures is a crucial problem in the hospital system. So, the advance of medical technology can press high costs, cutting off the manual process to faster and more effective system and efficiency costs of operational. The study uses Preferred Reporting Items for Systematic Review and Meta-Analyses (PRISMA), with many articles on the same issue. The same issues that can be found at the same topics of articles are probably more than fifty topics of articles. Articles were taken from various sources and database references, including Scopus 2 journals, Science Direct 16 journals, ProQuest 10 journals, Springer Link 3 journals, Google Scholar 36 journals, Research Gate 21 journals, PubMed 31 journals, and Emerald Insight 31 journals. So the total journal database is 133 journals. Then filtering was carried out by identifying the suitability of the journal until it was narrow and 27 articles were selected to be used as a reference in this research.. The purpose of this study is to determine the benefits of applying Electronic Medical Records in terms of economic, clinical, and access to clinical information. Some of the economic benefits include cost savings, effectiveness, and cost efficiency. Clinical benefits include reducing medical errors, improving data readability, improving the quality of care services, and increasing the productivity of medical personnel. And the benefits of accessing clinical information include improving the accessibility of patient history information, improving patient confidentiality, and assisting the decision-making process.